How to improve communication using technology in emergency medical services? A case study from Finland - Jari Haverinen; Maarit Kangas; Lasse Raatiniemi; Matti Martikainen; Jarmo Reponen (Finnish Social and Health Informatics Association, 2018)
The field of emergency medical services (EMS) is a challenging environment for ensuring fluent information exchange between stakeholders because several different kinds of organizations are involved in EMS missions. Solutions for information and communication technology can vary significantly depending on the organization. This study aims to identify current communication bottlenecks between EMS professionals, understand the technological challenges behind them, and describe technologies that can improve EMS communication in the future. Information for the study about current EMS processes, technologies, and technology needs was collected from EMS professionals during three workshops, five personal interviews, and one email questionnaire. All surveyed health care professionals were working in the county of Northern Ostrobothnia. Information about proposed technologies for EMS was obtained from literature and interviews with five technology companies. The principal problem in EMS communication is scattered health data. This leads to a lack of common situational awareness for professionals and incomplete medical histories for patients. The reasons behind those problems are different information systems which do not communicate with each other and the lack of a common electronic patient care record (ePCR) for use by stakeholders. Personal health measurements, sensors, telemedicine, and artificial intelligence will create opportunities for further improving the flow of communication in EMS, provided those tools can be integrated into decision-making systems.